Obstructive sleep apnea, sleep symptoms, and their association with cardiovascular disease. (18th September 2019) - Oh, Melissa S.; Bliwise, Donald L.; Smith, Andrew L.; Collop, Nancy A.; Quyyumi, Arshed A.; Dedhia, Raj C.
Abstract : Objectives: To determine the frequency of obstructive sleep apnea (OSA), insomnia, restless legs, and other sleep symptoms in patients with cardiovascular disease and the association of these sleep disorders with quantitative cardiovascular measures. Methods: Study design was a cross‐sectional survey and retrospective chart review. A questionnaire containing validated sleep symptoms was distributed to 202 patients with cardiovascular disease at a tertiary referral cardiology clinic. Following a focused review of these patients' medical charts, their questionnaire responses were examined for associations with clinical cardiovascular parameters. Results: Twenty‐one percent of patients reported a prior diagnosis of OSA. A total of 115 patients (60%) had at least one additional sleep symptom. Clinically significant insomnia was significantly associated with heart disease (relative risk [RR] = 1.5, confidence interval [CI] = 1.1 to 2.1), prior myocardial infarction or cerebrovascular accident (RR = 2.1, CI = 1.2 to 3.6), and heart failure (RR = 2.2, CI = 1.3 to 3.8). Left ventricular ejection fraction was significantly associated with insomnia by Insomnia Severity Index (β = −0.52, CI = −0.89 to −0.13). Conclusion: The frequency of OSA in patients in this tertiary cardiology clinic was higher than the general population in the United States, with the majority of patients experiencing at least one sleep symptom. Insomnia symptoms were shown to be associated with multiple cardiovascular measures, including left ventricular ejection fraction. These findings imply an interwoven relationship between cardiovascular and sleep symptoms as captured by validated sleep questionnaires. Level of Evidence: IV Laryngoscope, 130:1595–1602, 2020